Helicobacter pylori infection is associated with a reduced risk of developing eosinophilic oesophagitis - Von Arnim, U.; Wex, T.; Link, Alexander; Messerschmidt, M.; Venerito, M.; Miehlke, S.; Malfertheiner, P. (Alimentary Pharmacology & Therapeutics, 2016)
Background: Eosinophilic oesophagitis (EoE) represents a chronic immune-antigen-mediated allergic disease of the oesophagus of still unknown aetiology. Environmental exposure has been postulated to play a pathogenetic role. Helicobacter pylori (H. pylori) infection has been inversely associated with allergic diseases including atopic dermatitis, asthma and allergic rhinitis and H. pylori may play a protective role in these conditions. Little is known about the relationship between EoE and H. pylori. Aim: To investigate in a case-control study whether H. pylori infection is associated with a reduced risk of developing EoE. Methods: H. pylori infection was evaluated by serology in 58 [11(19%) female, 47 (81%) male, median age: 36.5 years, range 20-72 years] patients with a clinical and histologically proven diagnosis of EoE and 116 age and sex-matched controls (1 case: 2 controls). Antibodies against H. pylori were identified by enzyme-linked immunosorbent assay. Patients with H. pylori-specific IgG ≥30 enzyme immunounits were classified as H. pylori-positive. Results: 3/58 (5.2%) patients with EoE had serological evidence of H. pylori infection (EoE - H. pylori current infection) and 5/58 (8.6%) reported prior eradication therapy for H. pylori infection (EoE - H. pylori former infection). The control group demonstrated significantly higher seroprevalence of H. pylori (37.9%, P < 0.0001) when compared to patients with EoE. EoE was inversely associated with H. pylori infection [odds ratio (OR) 0.24, 95% confidence interval (CI) 0.11-0.50]. Conclusion: Helicobacter pylori infection is inversely associated with EoE. Our results may contribute to further understanding the pathogenesis and evolving aetiology of EoE.
CRIS-Team Scopus Importer:2025-10-13